Global perspectives for the management of onychomycosis. (25th December 2018) - Gupta, Aditya K.; Mays, Rachel R.; Versteeg, Sarah G.; Piraccini, Bianca Maria; Takwale, Anita; Shemer, Avner; Babaev, Meir; Grover, Chander; Di Chiacchio, Nilton G.; Taborda, Paulo R. O.; Taborda, Valeria B. A.; Shear, Neil H.; et al.
Abstract: Onychomycosis is a fungal nail infection caused by dermatophytes, nondermatophyte molds, and yeasts. This difficult‐to‐treat chronic infection has a tendency to relapse despite treatment. This paper aims to offer a global perspective on onychomycosis management from expert physicians from around the world. Overall, the majority of experts surveyed used systemic, topical, and combination treatments approved in their countries and monitored patients based on the product insert or government recommendations. Although the basics of treating onychomycosis were similar between countries, slight differences in onychomycosis management between countries were found. These differences were mainly due to different approaches to adjunctive therapy, rating the severity of disease and use of prophylaxis treatment. A global perspective on the treatment of onychomycosis provides a framework of success for the committed clinician with appreciation of how onychomycosis is managed worldwide.